Program doskonalenia chrześcijańskiego zawarty w ekshortacjach pastoralnych św. Cezarego z Arles (cz. II) - Celary, Ireneusz (Vox Patrum, 2025)
This article is the second part of a study of the programme of perfection proposed by St Caesarius of Arles. After presenting the first stage of perfection, encouraging the struggle against sins , the second part of our reflection will deal with the process of acquiring virtues, that is, in the broad sense of becoming more like Christ, based on the means of Christian perfection that the Bishop of Arles proposes to the recipients of his sermons as best serving Christian perfection. In these exhortations we note that he sought to give encouragement to the faithful striving for the ideal of holiness. For in them he pointed out that on the path of Christian perfection, they are not alone and on their own. For God gives everyone the possibility of perfecting themselves and supports them in this process by his grace. In this article, we would also like to point out that the teaching of St Caesarius continues to be held in high esteem in the Church and that, in the context of the new conditions, circumstances and circumstances of life, it is worthy of further scholarly reflection, presenting the relevance of this teaching to today's reality of the Church and the world.